Análisis de falencias como la disgrafía generada durante el contexto de la pandemia, en el proceso de enseñanza-aprendizaje del área de lengua y literatura en los niños de quinto año de educación general básica de la unidad educativa “Roberto Alfredo Arregui Chauvin” de la parroquia Gabriel Ignacio Veintimilla del cantón Guaranda, provincia Bolívar, Ecuador en el período lectivo 2022-2023. - Caluña Guamán, Edwin Johel (2023)
This study will seek the needs of reading comprehension in children from third to seventh year of basic education, looking for different strategies and teaching methods such as; creative games, and its purpose is to reach meaningful learning with this will be carried out the development of cognitive skills in students. That is why we have seen the need to investigate about creative games, to strengthen reading, and this will help the understanding of texts to be analyzed and understood, and the development of cognitive skills whose purpose will be a quality education and a better lifestyle. The paradigm of the investigation is socio-critical, since a theoretical investigation will be carried out and also of field, where data will be taken in a qualitative way, where the type of investigation will be descriptive, and the problems that the children present in reading will be identified, the instruments of data collection will be the interview and the observation card and it will be sought to raise a proposed solution to the raised problem Currently the lack of maintenance of reading corners and libraries have caused serious problems to society, there is little interest in reading, lack of motivation, lack of interest, has been degrading reading comprehension and as a result there is a high rate of linguistic difficulty. That is why we have seen the need through creative games, to strengthen reading, and this will help the comprehension of texts to be analyzed and understood, where their cognitive skills will be developed and its purpose will be a quality education and a better lifestyle. The paradigm of the investigation is socio-critical, since a theoretical investigation will be carried out and also of field, where data will be taken in a qualitative way, where the type of investigation will be descriptive, and the problems that the children present in the reading will be identified, the instruments of data collection will be the interview and the observation card and it will be sought to raise a proposed solution to the raised problem.Concluding the need to motivate and make dynamic the habit of reading, making known the benefits of reading, and thus improve their educational quality and lifestyle